Economic Estimation of a Green Ammonia Production System from Off Gas - Ruitao Sun; Jie Li; Li Sun (Chemical Engineering Transactions)
Most renewable ammonia plants developing from the conventional Haber-Bosch Process employ water electrolysis for hydrogen production and air separation for nitrogen production powered by renewables. Despite of the rapid development of technologies utilising renewables, the characteristics of intermittency and geographical limitation make it hard to eliminate stable fossil-based power plants and meet the continuous and increasing energy demands simultaneously. This work designs a green ammonia production system from off gas. The system integrates an amine-based carbon capture process for carbon removal from fossil-based power plants and nitrogen enrichment for nitrogen purification in Pressure Swing Adsorption (PSA), a hydrogen production process by PEM water electrolysis, and the Haber-Bosch Process. The system is modelled in Aspen Plus V12.1 and the equipment costs are obtained by a built-in economic model. The simulated data are used to estimate costs of raw materials and utilities. The total capital investment, total operating costs are evaluated in consideration of the chronological variation of the stack capital, LCOE, and carbon prices. The cost saving prevented from the carbon penalty proves the economic benefits of utilising off gas as nitrogen source. Generally in alignment with the predicted LCOA from IREA, the lowest LCOA is 936 $ t-1 in 2025 by employing onshore wind, 749 $ t-1 in 2035 by employing solar PV.